Identity Determinants of the Translocation Signal for a Type 1 Secretion System - Spitz, Olivia; Erenburg, Isabelle N.; Kanonenberg, Kerstin; Peherstorfer, Sandra; Lenders, Michael H. H.; Reiners, Jens; Ma, Miao; Luisi, Ben F.; Smits, Sander H. J.; Schmitt, Lutz (Frontiers in Physiology, 2022)
The toxin hemolysin A was first identified in uropathogenic E. coli strains and shown to be secreted in a one-step mechanism by a dedicated secretion machinery. This machinery, which belongs to the Type I secretion system family of the Gram-negative bacteria, is composed of the outer membrane protein TolC, the membrane fusion protein HlyD and the ABC transporter HlyB. The N-terminal domain of HlyA represents the toxin which is followed by a RTX (Repeats in Toxins) domain harboring nonapeptide repeat sequences and the secretion signal at the extreme C-terminus. This secretion signal, which is necessary and sufficient for secretion, does not appear to require a defined sequence, and the nature of the encoded signal remains unknown. Here, we have combined structure prediction based on the AlphaFold algorithm together with functional and in silico data to examine the role of secondary structure in secretion. Based on the presented data, a C-terminal, amphipathic helix is proposed between residues 975-987 that plays an essential role in the early steps of the secretion process..